Impact of Phosphorus Fertilization on Leaching, Accumulation, and Microbial Cycling in New Apple Orchards - Shen, Yuwen; Lin, Haitao; Xue, Rui; Ma, Yanan; Song, Yan (Agronomy (Basel), 2025)
Field experiments spanning five years were conducted to convert barren mountainous land into apple orchards, testing five phosphorus (P) fertilization schemes: no inorganic P (NP0K), superphosphate (FP), water-soluble inorganic P (WSF), superphosphate with alkaline soil conditioner (SC), and superphosphate with grass interplanting (GC). Fertilizer solubility and soil pH were found to significantly impact P leaching and accumulation. Among the schemes, WSF exhibited the highest P leaching loss (3.65–3.87%), while SC (2.17–2.79%) and GC (2.79–3.25%) minimized such losses. As soil pH declined over time, aluminum P (Al-P) replaced calcium P (Ca-P) as the dominant inorganic P fraction, while occluded P (O-P) increased, resulting in reduced P bioavailability. Soil organic carbon (SOC) and acid phosphatase activity positively influenced inorganic P fractions, whereas prolonged orchard establishment decreased fixed inorganic P content. Microbial P cycling genes were less abundant and showed negative correlations with soil nitrate-N, electrical conductivity, available P (Olsen P), and SOC. These findings highlight that grass interplanting with superphosphate (GC) is an optimal strategy to minimize phosphorus leaching, enhance soil phosphorus bioavailability, and reduce environmental risks, making it a sustainable approach for orchard management.